A critical evaluation of the social justice implications of the Colombian government's English-Spanish bilingualism policies. Issue 2 (14th March 2020) - Mackenzie, Lee
ABSTRACT: The National Bilingual Programme was launched in order to promote English learning in Colombia. The failure of this programme and subsequent iterations is well-documented, and research has also examined some of its negative effects for different societal groups. However, a comprehensive study of the social justice implications of Colombia's national bilingual programmes has not been carried out. Using Young's framework 'the five faces of oppression', the current paper shows how different groups experience different forms of injustice as a result of the implementation of Colombia's national bilingual programmes and their focus on language as a means to the end of economic development. It is argued that the the Colombian government's policy approach instrumentalises foreign language learning and diminishes the importance of the other purposes of learning a foreign language. Furthermore, this study shows how a lack of consideration of contextual factors from a social justice perspective can lead to shortcomings in policy implementation and the neglect of social justice issues. The conclusion suggests that bilingual policies need not be oppressive and outlines ways to ensure socially just English-Spanish bilingual education in Colombia.